Serum Tenascin-C and Alarin Levels Are Associated with Cardiovascular Diseases in Type 2 Diabetes Mellitus - Mingming Li; Mengjiao Wu; Hua Zhu; Yulin Hua; Zijun Ma; Jiayi Yao; Bin Feng; Bimin Shi (International Journal of Endocrinology)
Background. Tenascin-C (TNC), an extracellular matrix glycoprotein, is elevated in inflammatory and cardiovascular pathologies, whereas alarin, a novel orexigenic peptide, participates in insulin resistance and glycometabolism. The roles of these molecules in individuals with cardiovascular disease (CVD) and type 2 diabetes mellitus (T2DM), clinical conditions associating with metabolic disorders, and chronic inflammation, remain controversial. Our study aimed at determining the potential role of TNC and alarin in CVD adult patients with T2DM. Methods. This was a cross-sectional study. Basic and clinical information for 250 patients with T2DM were analyzed. Based on their cardiovascular disease status, participants were assigned into the CVD and non-CVD groups. Serum TNC and alarin levels were assessed by enzyme-linked immunosorbent assay (ELISA). Results. Serum TNC and alarin concentrations in the CVD group were significantly higher than those of the non-CVD group. Moreover, serum TNC levels were positively correlated with age, waist circumference, and waist-hip ratio; however, they were negatively correlated with TC, LDL-C, and eGFR levels. Alarin levels were positively correlated with BMI, waist circumference, and hip circumference. In logistic regression models, TNC and alarin were also established to be independent determinants for CVD in T2DM patients and their increases were associated with CVD severity. Receiver operating characteristic (ROC) curve analysis showed that the area under curve (AUC) values for TNC and alarin were 0.68 and 0.67, respectively. TNC and alarin were good predictors of CVD occurrence. When the cutoff value for TNC was 134.05 pg/mL, its sensitivity was 69.47% while its specificity was 61.29%. When the cutoff value for alarin was 142.69 pg/mL, sensitivity and specificity were 38.95% and 90.97%, respectively. Conclusion. Elevated TNC and alarin levels are independently associated with the occurrence and severity of CVD in T2DM individuals. Therefore, these two biomarkers are potential diagnostic and prognostic indicators for CVD in diabetics.